Overexpression of Ras‐GTPase‐activating protein SH3 domain‐binding protein 1 correlates with poor prognosis in gastric cancer patients. Issue 5 (19th May 2015) - Min, Lingqiang; Ruan, Yuanyuan; Shen, Zhenbin; Jia, Dongwei; Wang, Xuefei; Zhao, Junjie; Sun, Yihong; Gu, Jianxin
<x xml:space="preserve">Abstract</x> Aims Ras‐GTPase‐activating protein SH3 domain‐binding protein 1 (G3BP1) is a downstream effector of Ras signalling, and is overexpressed in several types of human malignancy. However, its role in gastric cancer remains unclear. The aim of this study was to investigate the prognostic significance of G3BP1 in gastric cancer. Methods and results G3BP1 mRNA and protein levels in paired frozen tumour samples were detected by real‐time polymerase chain reaction and western blotting, respectively. Paraffin‐embedded tumour samples were used for immunohistochemistry. Gastric cancer cells were used to detect the tumorigenic role of G3BP1 in vitro. We found that G3BP1 protein expression was markedly increased in gastric cancer tissues as compared with corresponding non‐malignant mucosa, whereas corresponding changes in mRNA levels were not observed. G3BP1 staining was positively correlated with tumour size, vascular invasion, T classification, lymph node metastasis, TNM stage, and reduced overall survival. Further analysis identified G3BP1 as an independent prognostic factor for poor prognosis, and combining G3BP1 with TNM stage generated a better predictive model for patient outcomes. G3BP1 also promoted proliferation, migration/invasion and extracellular signal‐related kinase and AKT activation in gastric cancer cells. Conclusions Our data define G3BP1 as a novel independent prognostic factor that is correlated with gastric cancer progression.